ANKHD1 promotes pathogenic proliferation in Autosomal Dominant Polycystic Kidney Disease via the Cyclin D1/CDK4 pathway - Maria-Eirini Terzenidou; Foteini Patera; Fiona M Macleod; Albert C M Ong; Maria Fragiadaki (Journal of Translational Medicine)
Abstract Background Autosomal Dominant Polycystic Kidney Disease (ADPKD) is the most common genetic cause of renal failure. Uncontrolled proliferation drives ADPKD, which manifests with cystic kidney enlargement. Yet, the mechanisms by which renal epithelial cells lose cell cycle control are largely unknown. To investigate this, we examined the expression and function of the Ankyrin Repeat and single KH Domain 1 (ANKHD1), which positively regulates proliferation in cancer, yet its role in ADPKD is unexplored. Results We report elevated proliferation (Ki67 and Cyclin D1) in three independent mouse models of ADPKD, the Pkd1 nl/nl , the Pax8-cre; Pkd1 del/del and the KSP-cre; Pkd1 del/del . We find that ANKHD1 protein localises in cyst lining cells of both aquaporin-1 and 2 (AQP1-AQP2) positive cysts. ANKHD1 knockdown in human cells or knockout in mouse tissues resulted in reduced proliferation, slower cystic growth in vitro and smaller kidneys in vivo; ultimately leading to improved renal function. Mechanistically, ANKHD1 binds to CDK4 and positively controls the Cyclin D1/CDK4 pathway. ANKHD1-mediated enhancement of Cyclin D1/CDK4 activity leads to increased retinoblastoma phosphorylation and proliferation, a mechanism that is p19-dependent but p21 independent. Conclusions We report a functional role for ANKHD1 in driving pathogenic proliferation in ADPKD via the Cyclin D1/CDK4 axis.